2003
DOI: 10.1046/j.1365-2222.2003.01689.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of nasal budesonide in the long‐term treatment of children with perennial rhinitis

Abstract: Long-term treatment for 1-2 years with intranasal budesonide 256-400 microg daily in children with perennial rhinitis revealed no negative effects on growth or endogenous cortisol production. Local side-effects were mild and patient symptoms decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 32 publications
2
42
0
2
Order By: Relevance
“…Ocular side effects such as evidence of cataracts, glaucoma or increased ocular pressure have not been shown in clinical trials to be associated with intranasal corticosteroid therapy [37,38,39,40] with the exception of 1 study with budesonide [41] and 1 study of fluticasone furoate [42]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular side effects such as evidence of cataracts, glaucoma or increased ocular pressure have not been shown in clinical trials to be associated with intranasal corticosteroid therapy [37,38,39,40] with the exception of 1 study with budesonide [41] and 1 study of fluticasone furoate [42]. …”
Section: Discussionmentioning
confidence: 99%
“…in 78 children with perennial AR, lenticular changes were found in 6 children [41]. Small lenticular opacities were present in 2 children at the start of the study and persisted through 12 months of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic absorption negligible with mometasone and fluticasone, modest for the remainder and high for betamethasone and dexamethasone -these should be used short term only [84][85][86]. Long-term growth studies in children using fluticasone, mometasone and budesonide have reassuring safety data, unlike beclomethasone [87][88][89][90][91]. Concomitant treatment with CYP3A inhibitors such as itraconazole or ritonivir may increase systemic bioavailability of intranasal corticosteroids [92,93].…”
Section: Topical Intranasal Corticosteroidsmentioning
confidence: 99%
“…Among studies based upon stadiometry measurements, only one reported a smaller mean increase in height among children treated with high-dose intranasal beclomethasone for 1 year compared with placebo (42). One-year studies involving mometasone furoate, fluticasone propionate, budesonide, and ciclesonide did not report any significant negative effects on height (43)(44)(45)(46). A 12-month double-blind study of ciclesonide in children found no significant difference in standing height between treated children and those using placebo (46).…”
Section: Derendorf and Meltzermentioning
confidence: 99%